2020
DOI: 10.3390/toxins12080514
|View full text |Cite
|
Sign up to set email alerts
|

The Tripartite Interaction of Host Immunity–Bacillus thuringiensis Infection–Gut Microbiota

Abstract: Bacillus thuringiensis (Bt) is an important cosmopolitan bacterial entomopathogen, which produces various protein toxins that have been expressed in transgenic crops. The evolved molecular interaction between the insect immune system and gut microbiota is changed during the Bt infection process. The host immune response, such as the expression of induced antimicrobial peptides (AMPs), the melanization response, and the production of reactive oxygen species (ROS), varies with different doses of Bt infection. Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 142 publications
(189 reference statements)
0
25
0
Order By: Relevance
“…aegypti since treated larvae were characterized by a lower bacterial diversity, compared to untreated individuals [ 399 ]. The interaction of Bt toxins with the midgut microbiota and the immune system of the insects was recorded, as reviewed by Li et al [ 400 ]. The microbiota can play a major role in the antiviral response of mosquitoes, either by secreting antiviral or proviral molecules or by modulating the immunity response [ 401 , 402 , 403 , 404 ].…”
Section: Impact On Life Traitsmentioning
confidence: 99%
“…aegypti since treated larvae were characterized by a lower bacterial diversity, compared to untreated individuals [ 399 ]. The interaction of Bt toxins with the midgut microbiota and the immune system of the insects was recorded, as reviewed by Li et al [ 400 ]. The microbiota can play a major role in the antiviral response of mosquitoes, either by secreting antiviral or proviral molecules or by modulating the immunity response [ 401 , 402 , 403 , 404 ].…”
Section: Impact On Life Traitsmentioning
confidence: 99%
“…Following the infection process of Bti , both the insect immune system and microbiota were changed. The activated immune response and dysbiosis of the microbiota have an important effect on the pathogenicity of Bti 52 . A better understanding of the abundance and compositional changes of bacteria could potentially be helpful to illuminating the interaction between Bti toxicity and microbiota, exploring available bacterial taxa strengthening Bti toxicity to mosquitoes, which finally contributes to the development of new sustainable mosquito control strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with these results, we also found enriched genes associated with the Toll and imd signaling pathway, which are two major immune pathways critical for the immune response that functions through the production of antimicrobial peptides (AMPs). AMPs are among the important members involved in humoral immune responses of insects 52 . The pronounced upregulation of gene expression associated with the Toll and imd signaling pathway indicated that larvae exposed to Bti mount a strong defense.…”
Section: Discussionmentioning
confidence: 99%
“…The intestinal microbiota contained in insects varies greatly with insect species, feeding habits, and living environment ( Xiao et al, 2017 ; Li S. et al, 2020 ). The intestinal microbiota of insects is found to be directly related to the physiological activities of the host, such as nutrient utilization, immune defense and regulation, metabolism, and development.…”
Section: The Resistance Mechanisms Of Insects Against Cry Toxinsmentioning
confidence: 99%